Formación docente a nivel de postgrado en Latinoamérica (2019)
It emphasizes the importance of research as an essential component of these academic programs and the challenges that must be posed by actors such as government, institutions, and teachers in order to contribute to the improvement of educational quality. From the methodological foundation, a reflective argumentative analysis allows the theoretical construction in attention to the main categories worked: Teacher Training - Postgraduate Studies - Educational Quality. Among the main results, it stands out that the different governments try to establish mechanisms that allow them to improve the control of the budget, but in their eagerness to achieve objectives referred to by international organizations such as the Organization for Economic Cooperation and Development (OECD), they establish policies that are not agreed upon with all the actors, including unions, which has resulted in negative consequences for educators. It is concluded that teacher training at the postgraduate level contributes to the improvement of educational quality by strengthening: the profile of competencies, didactic-pedagogical innovation, and promotion at the teacher level.